A warrior identity forged based on knee and elbow strikes: the narratives of the first masters of Brazilian muay thai (Revista de Artes Marciales Asiáticas, 2020)
The present study aimed to describe the main characteristics of muay Thai training carried out in the late 1970s and that, later, was the basis for Rudimar Fedrigo to set up the Chute Boxe academy and consolidate the identity of Brazilian muay Thai. Therefore, the following questions were posed: How were the trainings given by Nélio Naja in the beginnings of Brazilian muay Thai, through the memories of some pioneers of this practice? What are the nuances of the beginning of the identity construction of Brazilian muay Thai? In an attempt to answer such questions, hybrid oral history was used as a methodology. It was possible to conclude that the principles learned from grand master Nélio Naja, values based on training and intense physical conditioning, in addition to building a warrior identity, allowed the Chute Boxe academy to achieve world fame with victories in MMA, forged based on on knees and elbows.